Early Russian Cinema: The End of an Era The Revolutionary ; For Luck ; Behind the Screen - Bauer, Evgenij Francevic; Mozzuchin, Ivan Il'ic; Lissenko, Nathalie; Christie, Ian (British Film Institute, 1992)
Between the February and October revolutions in 1917, Russian cinema reflected urgent new themes, as in "The Revolutionary". But Bauer also continued his vein of tragic melodrama in what was be his last film, "For Luck" - designed by and featuring as an actor the young Kuleshov. A poignant fragment, "Behind the Screen", shows the stars Mozzhukhin and Lisenko on the eve of their departure into exile [Cover]
Keywords: DVD-Video